An African introduction to the New Testament - Abeneazer G. Urga; Mburu, Elizabeth W.; Okorie, Ferdinand I. (Minneapolis : Fortress Press, 2026)
"An African Introduction to the New Testament is the first of its kind to engage every book in the New Testament from the African context. Each of the chapters offers a thematic engagement of the book as well as the socio-cultural and religious heritage written by a wide array of scholars from across Africa"--
Keywords: New Testament ... Commentaries